PENGARUH PENERAPAN MEDIA PAPAN PERKALIAN TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS II SDN 04 KOTO BARU - Widia; Estika Hader, Antik; Ratnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low mathematics learning outcomes of students because in the learning process students still have difficulty understanding the learning material. For this reason, researchers conducted research using learning media. One of the learning media used is a multiplication board. This research aims to determine the effect of implementing multiplication board media on the mathematics learning outcomes of class II students at SDN 04 Koto Baru. The research method uses pre-experiment, with a one group pretest posttest design. The research subjects were all class II students at SDN 04 Koto Baru, totaling 28 people. The sampling technique in this research was saturated sampling with a sample size of 28 people. Data collection techniques in the form of pretest and posttest using test questions in the form of 20 multiple choice questions. data analysis technique using SPSS 20 using the Shapiro-Wilk test, with the criterion that if the results are significant, the results are more than 0.05, meaning they are normally distributed. Meanwhile, if the result is significant < 0.05, it means it is not normally distributed. So it can be concluded that the research results show that there is an influence of the application of multiplication board media on the mathematics learning outcomes of class II students at SDN 04 Koto Baru.